EDUCATIONAL INSTITUTIONS AND METHODS OF THEIR ELIMINATION (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
In improving the scientific and methodological training of students, it is important to ensure continuity between such educational courses as professional orientation in the teaching of specialty subjects, pedagogy, pedagogical technologies, psychology, which form professional training in the teaching of universal subjects, which are the basis of their scientific worldview and scientific theoretical training.